The role of high-resolution computerized tomography as a diagnostic tool in the evaluation and planning of management of patients with chronic otitis media - Monali Mitra; Priti Ashok Thakare; Berton Craig Monteiro; Dnyanesh B Amle (Wolters Kluwer Medknow Publications, 2021)
Context: Chronic otitis media (COM), a major cause of hearing impairment and its associated morbidity and mortality can be avoided with proper diagnosis and planned management. High-resolution computerized tomography (HRCT) is accessible and possesses role in the detection of COM. Aims: This study aims to evaluate the role of HRCT as a diagnostic tool in the evaluation and planning of management of patients with COM. Settings and Design: Prospective observational study. Subjects and Methods: The study included 100 subjects presenting with COM planned for detailed otorhinolaryngological and otoscopic examination, pure tone audiomentry, non-contrast HRCT of bilateral temporal bones and were exposed to initial medical management of symptoms and surgical management. Statistical Analysis Used: Data were expressed as percentage and mean ± standard deviation Kolmogorov-Smirnov analysis was performed for checking linearity of the data. Fischer's exact test or Chi-square test was used to analyze the significance of the difference between frequency distribution of the data. Results: For soft tissue attenuation, HRCT was 100% sensitive and specific for the presence of soft tissue mass. HRCT found to be 100% accurate in predicting cholesteatoma presence and was found to be sensitive in the range of 83.3%-100% and specific in range 87.04%-100%. For bony erosion, HRCT was found to be fairly accurate. These comparisons were found to be highly significant with P < 0.0001. Conclusions: HRCT of the temporal bone in subjects with COM can be a gold standard tool for diagnosis, surgical interventions, and follow-up.